The Relationship Between SNS Usage and Disordered Eating Behaviors: A Meta-Analysis - Zhang, Juan; Wang, Yihui; Li, Qianru; Wu, Chenggang (Frontiers in Psychology, 2021)
Social Networking Sites (SNSs) are common tools for modern people to share their lives and establish social relationships. SNSs were found to be associated with eating disorders in some studies, whereas other studies failed to identify the connection between SNSs and eating disorders. This study aimed to comprehensively synthesize previous studies using meta-analysis methods to explore the interaction between SNSs and eating disorder behaviors. There were 87 effect sizes from 22 studies based on our selection criteria. After analysis using a three-level random-effects meta-analysis model, we found a positive correlation between the use of SNSs and irregular eating behaviors, r = .09 (95% CI: .06, .11; p < .001). Besides, by analyzing potential moderators, we found that body mass index (r = -.032; 95% CI: -.058, -.006; p = .019), survey methods, and sample sources could alter the relationship between SNSs and disordered eating behaviors. Specifically, there was a significantly larger association between SNSs results obtained by paper and pencil and disordered eating behaviors (r = .114; 95% CI: 0.081, 0.147; p < .001) than that between SNSs results obtained online and disordered eating behaviors (r = -.055; 95% CI: -.102, -.007; p < .01). University students showed a larger correlation between SNSs and disordered eating behavior than other samples (r = .089; 95% CI: .049, .129; p < .001). Overall, this article confirms that the excessive use of SNSs is associated with increased risks of disordered eating behaviors. It is hoped that this study can provide a reference for the management and intervention of dietary behaviors related to social networks in the future.